Improving diabetes management of pregnant women in under-served communities of South Africa by using a mobile phone - Arbi, Shameela (Department of Human Biology, 2022)
Background Diabetes has been reported as being the tenth leading cause of death in South Africa, and can affect a person's livelihood, productivity and physical ability. In particular, gestational diabetes mellitus (GDM) affects 7-10% of pregnancies worldwide and greatly increases the risk of developing Type II diabetes after pregnancy, particularly if the patient has a high Body Mass Index. Research suggests that accurate education and proper management regarding diabetes can have a positive impact on the quality of patient life, as well as the country's healthcare system. One such disease management platform exists as mHealth, which is the acronym for mobile health, and is best described to be the use of mobile communication for health services and information. This report intends to Method The information for this report was gathered by means of a combination of Internet research, alreadyexisting knowledge of the subject, textbooks, journal articles, and thoughtful direction from the project supervisor. The research consisted of three studies: a systematic review, prototype design, and a user survey. The systematic review collected and analysed existing literature related to the knowledge and impact of mHealth among pregnant women with or at risk of GDM in underserved communities. The use of mHealth was analysed by focusing on its impact on outcomes related to glycaemic control, pregnancy and delivery, and behaviour and knowledge. This information was then used to develop a suitable mobile health platform targeted at a specific user: a pregnant woman. Design methods were used to identify the most effective solution, and a prototype was built using the online software Proto.io. User feedback on the produced prototype was received through an interview questionnaire, which was hosted by the online survey system SurveyMonkey. Results By paying close attention to parameters limited to under-served communities, the systematic review included four articles relevant to the scope of the research. Through the outcome analysis, the review revealed that two of the more common reasons for the development of GDM is a newly-pregnant woman being unaware of the risk, as well as lack of immediate access to available information on how to self-manage her pregnancy. It was identified that patient follow-up played a major role in helping them maintain weight and glucose goals, which is one of the driving factors behind the design of the intervention. Based on the requirements and specifications of the solution, a mobile application was chosen to be developed, in order to be able to develop a solution with the capability to meet a list of functions and features identified through the collected literature and user-based design. From the 33 respondents to the survey, it was discovered that majority (81.82%) of the respondents expressed competence in the use of mobile technology and had access to the internet and a smartphone. Most respondents (60.61%) specified that they preferred receiving knowledge in a ‘hands-on' capacity. Majority of the findings lined up with the collected literature as it was determined that the respondents believed having access to key medical and health information has a positive effect on the health outcomes of both mother and baby. Conclusions The investigation concluded that providing women with access to information and self-management platforms generally results in an increase in positive health outcomes for both women and their babies, during pregnancy and later in life. From the systematic review results, mobile health has a significant and positive impact on a patient's quality of life, as well as the healthcare industry. The results indicated technology can improve patient knowledge, understanding and management of GDM, though more research and controlled trials are required to support this deduction.